2011
DOI: 10.1007/s11096-011-9601-3
|View full text |Cite
|
Sign up to set email alerts
|

Application of ATC/DDD methodology to evaluate perioperative antimicrobial prophylaxis

Abstract: The density of antimicrobial use in PAP was found to be very high in our hospital. Antibiotic overuse extended into the postoperative period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 21 publications
0
15
0
5
Order By: Relevance
“…However because of lack of protocols, and hospital supply availability of antibiotics, personal judgments of treating physicians may explain the tendency to use broad spectrum or combination antibiotics and to continue use beyond 24 hours in our study. These findings are shared with Jordanian study which found that neither antibiotic choice(1.7%) nor duration(39.4%) were appropriate [12], the Turkish study [9] which also found that prolonged antibiotics prophylaxis was used in 56.9%, however the US study where protocols are usually followed showed excellent compliance (92.6%) in antibiotic selection [14]. …”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…However because of lack of protocols, and hospital supply availability of antibiotics, personal judgments of treating physicians may explain the tendency to use broad spectrum or combination antibiotics and to continue use beyond 24 hours in our study. These findings are shared with Jordanian study which found that neither antibiotic choice(1.7%) nor duration(39.4%) were appropriate [12], the Turkish study [9] which also found that prolonged antibiotics prophylaxis was used in 56.9%, however the US study where protocols are usually followed showed excellent compliance (92.6%) in antibiotic selection [14]. …”
Section: Discussionmentioning
confidence: 82%
“…Low adherence is shared by other studies in the region; For example the Jordanian study found that none of the observed cardiac operations was adherent to all antimicrobial prophylaxis guidelines with wide variation in adherence to selected parameters studied [12]. The Iranian study also found only one surgical procedure of the observed 155 to be adherent to all parameters of prophylaxis guidelines with varying degrees of compliance in different parameters [13], and the Turkish study found only 13.7% of the perioperative antibiotic prophylaxis given were appropriate and correct [9]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Anatomical Therapeutic Chemical (ATC) Classification System and the measurement unit of defined daily dose (DDD) [1] were recommended and officially regarded by the World Health Organization (WHO) as the international standard in drug utilization research (DUR) in 1996. The number of DDDs [2] and drug use density (DDDs per patient day [3], DDDs per 100 patient days [3][4][5][6], DDDs per 1000 patient days [7][8][9][10], DDDs per admission [3,11], DDDs per 1000 admissions [3,12,13], or DDDs per operation [14]) established based on the ATC/DDD system have been widely used as important indicators of antibiotic utilization research. However, although they can be obtained easily and applied to continuously and systematically monitor the administration of antibiotics in a population, these macro-indicators are not meaningful in evaluating the appropriateness of drug utilization.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, almost surgery should be given prophylactic antibiotics to reduce the incidence of SSI. The use of appropriate antibiotic prophylaxis in surgery is quite effective in reducing mortality and health care costs associated with infection after surgery [3]. However, the compliance to surgical guidelines for antibiotic prophylaxis in some countries is still varies including in Indonesia [4][5][6].…”
Section: Introductionmentioning
confidence: 99%